2001
DOI: 10.1046/j.1365-2648.2001.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of self‐determination as expressed in the context of care

Abstract: Patients' perceptions of self-determination suggest that, in their encounters with the professional care, knowledge is expressed as power. The feeling of a lack of self-determination can be reduced by help and support from a nurse who allocates time for communication in order to learn the patient's needs and reach a mutual understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 32 publications
7
83
0
4
Order By: Relevance
“…In the present study, the patients reported they felt that the personnel lacked time and they wished staff members would be more sensitive to their wishes and needs. Similar findings were obtained in another study (Nordgren & Fridlund 2001). Thus staff should remember that tone of voice, attitude and character in meeting with the patient are crucial in deciding how the relationship with the individual patient develops.…”
Section: Perceptions Of Receptionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the present study, the patients reported they felt that the personnel lacked time and they wished staff members would be more sensitive to their wishes and needs. Similar findings were obtained in another study (Nordgren & Fridlund 2001). Thus staff should remember that tone of voice, attitude and character in meeting with the patient are crucial in deciding how the relationship with the individual patient develops.…”
Section: Perceptions Of Receptionsupporting
confidence: 66%
“…Sometimes the patients dare not ask questions and express their doubts. A reason can be that when doctors and other members of the staff on the basis of their knowledge and proficiency are given the opportunity for disciplined exercise of power (Raatikainen 1994), the patients surrender to their decisions, in order not to be considered troublesome (Nordgren & Fridlund 2001). …”
Section: Perceptions Of Postponements/cancellations Caused By Organizmentioning
confidence: 99%
“…The fact that a power imbalance exists between the nurse and the patient has also been shown by Johnson and Webb (1995), who found that the nurse-patient relationship often can be seen as a struggle, where patients are forced to fit predefined nursing goals. This struggle was also expressed by Swedish patients when asked about their perceptions of self-determination, where they felt their own will collided with that of staff (Nordgren and Fridlund, 2001). Our study is the first to show a connection between losing power struggles and feeling abused in health care.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 Self-agency is a construct from psychological research that appears to be particularly relevant to patient-centered care and patient empowerment. 22,23 Additionally, self-agency is also linked to outcome expectations for patients. 22,23 Lastly, a great deal of research has shown that people's attachment styles may mediate their perceptions of others as trustworthy and approachable, which may emerge in the discussions and general interactions between physicians and patients.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…22,23 Additionally, self-agency is also linked to outcome expectations for patients. 22,23 Lastly, a great deal of research has shown that people's attachment styles may mediate their perceptions of others as trustworthy and approachable, which may emerge in the discussions and general interactions between physicians and patients. 24 In the current study, we bring these concepts together to examine their interplay with the working alliance and to see how well each explains patient satisfaction and adherence.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%